Role of Early Life Cytotoxic T Lymphocyte and Natural Killer Cell Immunity in Paediatric HIV Cure/Remission in the Anti-Retroviral Therapy Era - Vieira, Vinicius A.; Herbert, Nicholas; Cromhout, Gabriela; Adland, Emily; Goulder, Philip (Frontiers in Immunology, 2022)
Only three well-characterised cases of paediatric HIV functional cure cases have been described over the past decade. This underlines that early initiation of combination antiretroviral therapy (cART), minimises the viral reservoir size, but is insufficient to achieve cure, unless other factors contribute. In this review, we consider these additional factors that may facilitate functional cure in paediatric infection. Among the early life immune activity, these include HIV-specific cytotoxic T-lymphocyte (CTL) and natural killer (NK) cell responses. The former have less potent antiviral efficacy in paediatric versus adult infection, and in early life, NK responses have greater impact in suppressing viral replication than CTL. This may contribute to a greater functional cure potential in paediatric versus adult infection, since post-treatment control in adults is associated less with highly potent CTL activity, and more with effective antiviral NK cell responses. Nonetheless, antiviral CTL responses can play an increasingly effective role through childhood, especially those expressing the ‘protective’ HLA-I molecules HLA-B*27/57/58:01/8101. The innate system role on preventing infection, in shaping the particular viruses transmitted, and influencing outcome is discussed. Female fetus susceptibility to in-utero mother-to-child transmission, especially in the setting of recent maternal infection, provides clues to mechanisms by which cure may be achieved, since initial findings are that viral rebound is less frequent among males who interrupt cART. The potential of broadly neutralising antibody therapy to facilitate cure in children who have received early cART is discussed. Finally, the impact of the changing face of paediatric HIV epidemic on cure potential is discussed. The effect of cART is not limited to preventing AIDS and reducing the risk of transmission. cART also affects which mothers transmit. No longer are mothers who transmit those who carry genes associated with poor immune control of HIV. In the cART era, a high proportion of transmitting mothers have seroconverted in pregnancy or who are diagnosed late in pregnancy. Therefore, genes associated with poor immune control of HIV are not enriched in mothers who transmit HIV to their child. These changes will likely influence the effectiveness of HLA-associated immune responses and therefore cure potential among children.